Phase and group velocities of ectromagnetic eigen waves of left-hand material slab - Azarenkov, N.A.; Galaydych, V.K.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2012)
This work is devoted to the study of phase and group velocities of the surface eigen electromagnetic waves that propagate along the left-handed planar slab that bounded by the dielectrics with different permittivity values at the both sides of considered slab. It has been shown that the change of metamaterial slab thickness substantially influences on dispersion of the waves under investigation.